2019
DOI: 10.3892/ol.2019.10172
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone induces gastric cancer BGC‑823 cell apoptosis by regulating reactive oxygen species generation and the AKT signaling pathway

Abstract: Alantolactone (ALT), a natural sesquiterpene lactone, has been suggested to exert anti-cancer activities in various cancer cell lines. However, the effects and mechanisms of action of ALT in human gastric cancer remains to be elucidated. In the present study, the effects of ALT on BGC-823 cells were examined and the underlying molecular mechanisms associated with these effects were investigated. Cell viability was detected by using an MTT assay. Cell cycle, cell apoptosis and the level of reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Thus, the Pi3K/aKT signaling pathway may represent a possible target for cancer therapy in osteosarcoma. alantolactone (alT) is a biologically natural compound derived from Inula helenium (17). Previous studies have reported that alT promotes numerous biological effects, including anti-inflammatory and antioxidant functions (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the Pi3K/aKT signaling pathway may represent a possible target for cancer therapy in osteosarcoma. alantolactone (alT) is a biologically natural compound derived from Inula helenium (17). Previous studies have reported that alT promotes numerous biological effects, including anti-inflammatory and antioxidant functions (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…ALT has been shown to contribute to cell apoptosis in several types of cancer. For example, ALT induces gastric cancer BGC-823 cell apoptosis by regulating the AKT signaling pathway [21]. ALT induces apoptosis of breast cancer cells via the p38 MAPK, NF-κB and Nrf2 signaling pathways [22].…”
Section: Discussionmentioning
confidence: 99%
“…ALT has been shown to contribute to cell apoptosis in numerous cancers. For example, ALT induces gastric cancer BGC-823 cell apoptosis by regulating the AKT signaling pathway [19]. ALT induces apoptosis of breast cancer cells via the p38 MAPK, NFκB, and Nrf2 signaling [20].…”
Section: Discussionmentioning
confidence: 99%